A política pública de saúde no Brasil: dilemas e desafios para a institucionalização do SUS - Silva, Heliana Marinho da (1996)
The present study analyzes the conditions of implementation of the Sistema Único da Saúde - SUS (Health System), identifying dilemmas and challenges involved in its institutionalization. A synthesized history of Public Health Policy in Brazil highlights the dichotomies between preventitive measures developed by the Ministry of Health, and curative measures carried out by the Ministry of Social Welfare. The investigation reveals that a return to the process of formulation and implementation of integrated and decentralized health programs is of fundamental importance for the consolidation of SUS and its proposed programs that are based on the constitutional mandates of universality, integrality, decentralization and popular participation in the administration of the hea1th system. The degree of success of this consolidation depends on the levei of ability and skill in the different govemmental entities, the levei of responsiveness to the population, and the possibilities for future funding of the system.